Successful containment of Covid‐19 outbreak in a large maternity and perinatal center while continuing clinical service. Issue 5 (17th May 2020) - Kabesch, Michael; Roth, Samra; Brandstetter, Susanne; Häusler, Sebastian; Juraschko, Eva; Weigl, Marco; Wellmann, Sven; Lang, Thomas; Schmidt, Barbara; Salzberger, Bernd; Ambrosch, Andreas
Abstract: With increasing number of SARS‐CoV‐2 infections and COVID‐19 patients to be taken care of by the health system, more and more health workers become affected by the disease. It has been reported that right from the beginning of the outbreak in Lombardy up to 20% of the doctors and nurses became infected. Under these circumstances, the regular operation of health institutions already suffering from a shortage of staff becomes difficult. This has led to complete or partial shutdowns of hospitals, either due to a lack of uninfected personnel or because of uncontrollable chains of infection endangering patients. In one of the largest university perinatal center in Bavaria with more than 3000 births per year, an outbreak of COVID‐19 occurred in March 2020, affecting 36 staff members, including doctors, nurses, and midwives. Here, we describe the outbreak and present the measures contributing to the successful containment of the outbreak within three weeks. At the same time, clinical services could be maintained, however, not without deployment of personnel exposed to employees infected with SARS‐CoV‐2. Apart from massive testing of personnel in pre‐defined phases and increased hygiene measures, including a general obligation to wear surgical face masks, we identified the need to monitor cases of illness across all groups of employees, to ensure social distancing within personnel and to evaluate contacts of clinical personnel outside of the hospital environment, in order to be able to interpret chains of infections and to disrupt them. Overall, only a bundle of measures is needed to contain such an outbreak.